Psychosocial problems and acceptance in the coming-out process among non-heterosexual males. - Ponsaran, Marie Cris V; Trabado, Pamela A.
This is a qualitative study aimed to determine the problems and acceptance by non-heterosexual males and other the society in the coming-out process. Eight of the respondents are self-confessed bisexuals and four are homosexuals chosen through snowball sampling technique., Researchers used unstructured questionnaires in gathering data, asking about coming-out, its effects and how respondents coped and was analyzed through qualitative data analysis. Results revealed that 50 percent of the respondents experienced confusion about their sexual identity during elementary whereas, 33 percent of them accepted it at high school and college, respectively, Majority disclosed during high school because they wanted to be free from pretensions. Moreover, being true to themselves are said to be effects of coming-out in their emotional and social development. In general most respondents accepted their sexual orientation positively but there were some who had initial negative reactions because of the stigma attached to being gay.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Non-heterosexual males -- Psychological aspects